The influence of supervisory board composition on discretionary accruals in China - Li, Mengjia; Fauzi Saidin, Saidatunur; Lau, Yeng Wai; Teng, Jingxuan (Human Resource Management Academic Research Society, 2024)
Effective corporate governance (CG) is crucial in mitigating earnings management, especially in emerging economies like China, where the two-tier board system presents unique challenges and opportunities. This study examines the impact of supervisory board (SB) composition on discretionary accruals (DA) in Chinese listed companies, emphasizing the importance of SBs in enhancing CG practices. Limited research had adopted in SB under the two-tier CG structure, even less had investigated the field of the SB composition with DA. Moreover, previous research on SB mainly based on developed countries like German and Japan, it is necessary and urgent to examining the effectiveness of SB in constraining DA in emerging economy like China. Based on 3,094 listed companies on Shanghai and Shenzhen Stock Exchange during 2018 to 2022, the fixed effects regression model is conducted through the balanced panel data of 15,470 observations to test the hypotheses. Result shows SB size is negatively related with DA, while female supervisors and labor representatives in SB significantly constrain firm level DA. Supervisor’s financial background presented no significant impact on inhibiting DA. The result is robust and stable through a series of alternative tests addressed multicollinearity issue and endogeneity problems. Empirical results from China, the world’s second-largest economy, offers valuable insights and serves as a guide for emerging economies and countries considering adopting the two-tier system to enhance CG structure. Future research can adopt qualitative methodology like in-depth interview or semi-structure interviews to explore the personal characteristics of supervisors in detail and corresponding impacts on CG.